2015
DOI: 10.1371/journal.pone.0138046
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Off-Hour Emergency Care in Acute Ischemic Stroke: Results from the China National Stroke Registry

Abstract: Background and PurposeThe quality of after-hour emergency care of patients with acute ischemic stroke is debatable. We therefore, sought to analyze the performance measures, quality of care and clinical outcomes in these patients admitted during off-hours.MethodsOur study included 4493 patients from a selected cohort of patients admitted to the hospitals with ischemic stroke in the China National Stroke Registry (CNSR) from September 2007 to August 2008. On-hour presentation was defined as arrival at the emerg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…[21][22][23][24][25] On the contrary, several studies found that off-hour admission was not associated with an unfavorable outcome in acute ischemic stroke patients. [26][27][28][29][30][31][32] As for pulmonary embolism, hospitalization on weekends seemed to be associated with a signi cantly higher mortality rate than hospitalization on weekdays in two publications. 3,33 Taiwan has commenced a universal NHI program, nanced jointly by payroll taxes, subsidies, and individual premiums, since 1995.…”
Section: Discussionmentioning
confidence: 98%
“…[21][22][23][24][25] On the contrary, several studies found that off-hour admission was not associated with an unfavorable outcome in acute ischemic stroke patients. [26][27][28][29][30][31][32] As for pulmonary embolism, hospitalization on weekends seemed to be associated with a signi cantly higher mortality rate than hospitalization on weekdays in two publications. 3,33 Taiwan has commenced a universal NHI program, nanced jointly by payroll taxes, subsidies, and individual premiums, since 1995.…”
Section: Discussionmentioning
confidence: 98%
“…Several observational studies have assessed the ‘off-hour effect’ in patients with IS. Prior studies have reported incoherent results on whether off-hour admission is associated with worse outcome after IS [ 5 , 22 , 24 , 28 ] or not [ 4 , 10 , 13 , 15 , 19 , 27 , 29 ]. In a retrospective study of 26676 IS subjects from the Hospital Morbidity Database of 606 hospitals in Canada, Saposnik et al [ 25 ] reported that weekend admission was associated with early mortality, which was similarly observed among subjects presented to urban versus rural medical centers or specialist versus a general practitioner.…”
Section: Discussionmentioning
confidence: 99%
“…However, the difference in incidence and quality of care between the two groups disappeared after adjusting for pre-hospital delay and other variables. 12…”
Section: Stroke Care Quality Benchmark In Chinamentioning
confidence: 99%